Use of SeedCounter Mobile App for Wild Species Seed Number Determination: A Preliminary Study - Farid Kuswantoro (Nusantara Science and Technology Proceedings)
Although its simple nature, seed counting is a crucial but demanding process in seed research and conservation. Manual seed counting, which usually takes a lot of effort and time, needs to be supplemented by new, easy-to-use, and accurate tools to simplify the process. Fortunately, the advance of information technology in recent years is significantly easing daily human life, including seed conservation and research. SeedCounter (https://cutt.ly/xhZFMZk) is a smartphone app which could help seed scientist to perform their seed counting process. However, as wild plant seeds come in various sizes, forms, and shapes, the app's ability to perform seed count of wild plant seeds need to be understood entirely. Thus, this study aims to understand the SeedCounter app's ability to perform seed counting in 20 wild plant seeds collected in Bali Botanic Garden Seed Bank Laboratory. We hope that the study will provide preliminary data for the app's potential to help seed conservation and research future efforts. SeedCounter app is downloaded and installed in a Nokia 6.1 Plus smartphone. Seeds photographed using the app with three replications conducted for each of the species. Seed counting is defined as a success if the app can count the seed number three consecutive times correctly. Data analysis was conducted descriptively. The study result showed that the SeedCounter app could correctly count seeds of ten plant species, which compares with 50% of the tested species. The result highlights SeedCounter's potential to simplified the counting process of some wild plant species seed.